2019
DOI: 10.1002/jso.25403
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative outcomes of extensive bowel resection during cytoreductive surgery in patients with advanced ovarian cancer

Abstract: Background and Objectives To achieve optimal cytoreduction, extensive bowel resections are sometimes required in patients with advanced ovarian cancer. Few studies have focused on the extent or number of resections of bowel surgeries and their feasibility. Methods We retrospectively reviewed the medical records of patients with advanced ovarian cancer who underwent bowel surgery as part of debulking procedures at Ajou University Hospital from 2006 to 2018. Patients who received extensive bowel resections (two‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 22 publications
(59 reference statements)
1
16
0
Order By: Relevance
“…However, the rate of anastomotic leakage was not significantly different between the 2 periods, and the rate of protective ileostomy was lower during the post-learning period than during the initial learning period because the intraoperative blood loss in post-learning period was less than in initial period. We showed that rectosigmoid resection with anastomosis for advanced ovarian cancer can be performed safely even without routine performance of protective ileostomy and that multiple bowel resections did not increase the risk of anastomotic leakage, which is compatible with previously reported studies describing this subject [3738].…”
Section: Discussionsupporting
confidence: 90%
“…However, the rate of anastomotic leakage was not significantly different between the 2 periods, and the rate of protective ileostomy was lower during the post-learning period than during the initial learning period because the intraoperative blood loss in post-learning period was less than in initial period. We showed that rectosigmoid resection with anastomosis for advanced ovarian cancer can be performed safely even without routine performance of protective ileostomy and that multiple bowel resections did not increase the risk of anastomotic leakage, which is compatible with previously reported studies describing this subject [3738].…”
Section: Discussionsupporting
confidence: 90%
“…Ovarian cancer often spreads along the peritoneal surface and invades the bowel serosa and mesentery (9). According to a previous study, 72% of the advanced ovarian cancer patients had visible tumor in the small and large bowels (13).…”
Section: Discussionmentioning
confidence: 99%
“…The bowel resection rate during cytoreductive surgery ranged from 40-80% in institutions adopting radical surgery (12,(14)(15)(16). Two recent publications evaluated multiple bowel resections in ovarian cancer, one from Germany (12) and one from Korea (9). Given the small number of patients with anastomotic leak, we did not assess the underlying risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subgastric omentectomy is performed by dissecting the gastro colic ligament below the stomach also the gastrosplenic ligament is excised on the left (Figure 18a) (care is taken to avoid splenic laceration and bleeding while dealing with splenic ligament), as well as the omental bursa is exposed, examined the lesser omentum and the retroperitoneal organs of the upper abdomen 19,20 . In some cases, the resection of the lesser/greater omentum is performed to achieve tumor-free area (Figure 18b).…”
Section: Guest Editorialmentioning
confidence: 99%